Improving distress perception and mutuality in migraine caregivers after 6 months of galcanezumab treatment. Issue 9 (7th October 2022) - Fofi, Luisa; Altamura, Claudia; Fiorentini, Giulia; Brunelli, Nicoletta; Marcosano, Marilena; Barbanti, Piero; Vernieri, Fabrizio
Abstract: Objective: This prospective cohort, real‐life study aimed to evaluate whether galcanezumab, a monoclonal antibody anti‐calcitonin gene‐related peptide (CGRP) ligand, can reduce caregivers' distress and improve their mutuality with patients. Background: Migraine is a highly disabling chronic disease that negatively impacts patients' and often their relatives' lives, occurring during an active phase of life with direct consequences on leisure‐ and work‐related activities. The figure of caregiver is crucial in several neurological conditions but poorly accounted for in migraine care so far. Studies on monoclonal antibodies against the CGRP pathway, recently introduced as migraine‐preventive treatments, demonstrated that they significantly reduce migraine frequency and disability in the first weeks of treatment. Methods: Consecutive patient‐caregiver dyads were evaluated at baseline and after 6 months of treatment with galcanezumab (V6) at our headache center from September 2020 to September 2021. Enrolled patients were requested to report their monthly migraine days, monthly intake of acute medications, attack pain intensity (on the Numeric Rating Scale), concomitant preventives, and disability questionnaires (Headache Impact Test, Migraine Disability Assessment). Each dyad filled in the Mutuality Scale to check their reciprocity; moreover, the Relatives' Stress Scale was used to detect caregivers' distress. Results: We enrolled 27 patient‐caregiver dyads. At 6 months, migraine burden significantly improved with reductions in monthly migraine days (falling from 14.8 [SD = 4.8] days by 10.3 [SD = 4.8] days; 95% CI: 8.4, 12.2; p < 0.001) and Migraine Disability Assessment scores (lowering from 83.6 [SD = 46.7] by 71.5 points [SD = 49.3]; 95% CI: 51.2, 91.9; p < 0.001). From baseline to month 6, the caregiver Relatives' Stress Scale score significantly decreased (falling from 20.7 [SD = 13.7] by 6.5 [SD = 14.1] points; 95% CI: 0.8, 12.2; p = 0.027), while the Mutuality Scale's caregiver total score increased (from 3.04 [SD = 0.61] by 0.29 [SD = 0.49] points; 95% CI: −0.508, −0.064; p = 0.014). Conclusions: Our findings preliminarily demonstrated that patients' migraine improvement after 6 months of galcanezumab treatment could be favorably perceived by caregivers, significantly reducing their distress with better reciprocity within the dyad.